Contratos relacionais na indústria aeronáutica brasileira: um estudo empírico do modelo de parcerias de risco da Embraer - Ribeiro, Thiago Alves (2012)
This work is an empirical study of the contractual practices adopted by Embraer after its privatization in 1994. We also analyze the contractual arrangement used to enable the aircrafts’ projects that were responsible for the company's resurgence in the late 1990s. A fundamental aspect of the contractual engineering efforts was the creation of Risk-Partnerships between Embraer and a selected group of key suppliers to co-develop an aircraft. The analysis of the collected data, points to the epistemological relevancy of using new analytical tools to understand the contractual practices that have been employed and its role in development. Therefore, we adopt the relational contract theory as a theoretical lens to analyze the risk-partnership model and investigate the role played by relational elements in the success of the ERJ 145 and EMBRAER 170/190 programs. The central hypothesis that guides this work states that, in the innovative contractual arrangement involving Embraer, foreign suppliers and BNDES, the contractual relationship was built through promissory and non-promissory mechanisms that have projected the exchange, and the patterns of normativity that were created transcended the written contract. The contribution of relational contract theory to the analysis of such practices is twofold. The first contribution is mainly descriptive, as it provides more comprehensive and powerful theoretical tools to understand the real dynamics of the contractual practices that have been studied. The second contribution, of a normative kind, consists in clarifying the relational aspects that compose, alongside promissory elements, a certain internal normativity to the contract, which regulates the agents’ conduct throughout the relationship. On the ERJ 145 and EMBRAER 170/90 programs, we try to demonstrate that (more) relational contractual arrangements, instead of conventional discrete contractual supplying relationships, were critical to the success of the projects and even for their own feasibility. In this sense, relational contracts theory provides analytical categories that not only offer more adequate theoretical tools to describe relationships such as the one under study, but also provides, through a more rich and comprehensive description, lessons on how to design contracts. This is important to demonstrate how the problem of the implicit dimensions of contracts transcends the field of contract theory and contractual justice and becomes highly relevant to the research agenda in the Law and Development field.